Comparative Effects of Dynamic Stretching and Ice Bag Application On the Physical Performance in Recreational Basketball Players: A Randomized Crossover Study - Kumar, Ajit; Verma, Nishank; Hussain Khan, Moazzam; Bhattacharya, Sudip (Indian Journal of Community Health, 2022)
Introduction: Researchers found that cryotherapy at the ankle joint heightened adjacent muscle activity and reflex amplitude, which facilitated greater force production at the ankle complex. Furthermore, cryotherapy appears to increase musculoarticular stiffness, which has been associated with heightened muscular performance at a joint. Aim and objective: the aim of the study is to examine the influence of dynamic stretching and IBA technique on the physical performance. Methodology: Total 20 healthy male basketball athletes encompassing two groups participated in the current study. The study consisted of two groups, Group A (ice bag application) and Group B (dynamic stretching). Cold compress was applied over the anterior thigh, posterior thigh, and calf. Subjects were assigned to Group A, and Group B, using Convenience sampling method. Each candidate performed the 5 minutes of jogging before taking intervention. All subjects performed three functional performance tests: Vertical Jump Test, Agility T-test & 20-meter sprint. Each participant attended an orientation session to become familiar with the testing procedures. Subjects were randomly assigned into two groups and exposed to a crossover study design. The experiment was performed on two separate occasions whereby one group received the dynamic stretching in the first session, while the other group uses the cryotherapy first. After 48 hours, (cooling session) on the next occasion, the groups were changed and the second group receives the cryotherapy, while the first group performs dynamic stretching. On both occasions, the dynamic stretching and cryotherapy interventions were the same. Between the sessions, the subjects will not allow to participate in any kind of vigorous physical activity. Results: The present study showed an increase in performance of recreational Basketball players by the combination of 5 minutes of warm up plus 6 min of dynamic stretching on the vertical jump height and 20-meter sprint.